Metabolites in the regulatory risk assessment of pesticides in the EU - Pelkonen, Olavi; Abass, Khaled; Parra Morte, Juan Manuel; Panzarea, Martina; Testai, Emanuela; Rudaz, Serge; Louisse, Jochem; Gundert-Remy, Ursula; Wolterink, Gerrit; Jean-Lou CM, Dorne; Coecke, Sandra; Bernasconi, Camilla (Frontiers in Toxicology, 2023)
A large majority of chemicals is converted into metabolites through xenobiotic-metabolising enzymes. Metabolites may present a spectrum of characteristics varying from similar to vastly different compared with the parent compound in terms of both toxicokinetics and toxicodynamics. In the pesticide arena, the role of metabolism and metabolites is increasingly recognised as a significant factor particularly for the design and interpretation of mammalian toxicological studies and in the toxicity assessment of pesticide/metabolite-associated issues for hazard characterization and risk assessment purposes, including the role of metabolites as parts in various residues in ecotoxicological adversities. This is of particular relevance to pesticide metabolites that are unique to humans in comparison with metabolites found in in vitro or in vivo animal studies, but also to disproportionate metabolites (quantitative differences) between humans and mammalian species. Presence of unique or disproportionate metabolites may underlye potential toxicological concerns. This review aims to present the current state-of-the-art of comparative metabolism and metabolites in pesticide research for hazard and risk assessment, including One Health perspectives, and future research needs based on the experiences gained at the European Food Safety Authority. Deleted: With regards to pesticide risk assessment, a key 178 requirement is the rat in vivo toxicokinetic study, providing general 179 toxicokinetic information including rate and extent of absorption, 180 distribution, excretion, metabolism, metabolite identification and 181 characterisation produced in vivo as laid down in the Organisation for 182 Economic Co-operation and Development (OECD) TG417 and 183 illustrated with three examples in table 1. ¶ 184 Deleted: complex outcomes of primary metabolism, a survey 185 conducted by Abass et al. (2012) delved into the role of human 186 recombinant cytochrome P450 isoforms in the metabolism of 63 187 different pesticide active substances. A…